Creative writing - Pearson, Mark; Foster, Helen (Emerald Publishing Limited, 2024)
Diving into this beloved practice, Creative Writing explores how the written word can be used as a therapeutic tool in pursuit of improved mental health and wellbeing. Exploring a variety of settings, including group writing, writing alone, and even workshopping online, pracademic duo Mark Pearson and Helen Foster design and deliver a series of contemporary case studies related to mental health, menopause, mindfulness and psychosis. Imagining new, introspective outlets for the support of mental and physical wellbeing, Pearson and Foster draw on their clinical and archival expertise to equip both healthcare professionals and general readers to unleash their creativity and unlock the comfort and creativity that putting pen to paper can bring.
Includes index.
Keywords: Creative writing -- Psychological aspects.; Mental health.; Medical -- Mental Health.; Popular medicine and health.; Psychiatric and mental disorders.; elektronické knihy; electronic books